Cold-passaged isolates and bat-swine influenza a chimeric viruses as modified live-attenuated vaccines against influenza a viruses in pigs. Issue 43 (12th October 2022) - Graaf, Annika; Petric, Philipp P.; Sehl-Ewert, Julia; Henritzi, Dinah; Breithaupt, Angele; King, Jacqueline; Pohlmann, Anne; Deutskens, Fabian; Beer, Martin; Schwemmle, Martin; Harder, Timm
Abstract: Swine influenza A virus (swIAV) infections in pig populations cause considerable morbidity and economic losses. Frequent reverse zoonotic incursions of human IAV boost reassortment opportunities with authentic porcine and avian-like IAV in swine herds potentially enhancing zoonotic and even pre-pandemic potential. Vaccination using adjuvanted inactivated full virus vaccines is frequently used in attempting control of swIAV infections. Accelerated antigenic drift of swIAV in large swine holdings and interference of maternal antibodies with vaccine in piglets can compromise these efforts. Potentially more efficacious modified live-attenuated vaccines (MLVs) bear the risk of reversion of MLV to virulence. Here we evaluated new MLV candidates based on cold-passaged swIAV or on reassortment-incompetent bat-IAV-swIAV chimeric viruses. Serial cold-passaging of various swIAV subtypes did not yield unambiguously temperature-sensitive mutants although safety studies in mice and pigs suggested some degree of attenuation. Chimeric bat-swIAV expressing the hemagglutinin and neuraminidase of an avian-like H1N1, in contrast, proved to be safe in mice and pigs, and a single nasal inoculation induced protective immunity against homologous challenge in pigs. Reassortant-incompetent chimeric bat-swIAV vaccines could aid in reducing the amount of swIAV circulating in pig populations, thereby increasing animal welfare, limiting economic losses and lowering the risk of zoonotic swIAV transmission.